The Discovery of HR from Strategy-as-Practice Perspective: A case study in durable consumer goods industry - GÜRBÜZ, FATMA GÜLRUH (ELSEVIER SCIENCE BV, 2015)
The aim of this study is to explore Human Resource Management (HRM) practices from Strategy-as-Practice (S-as-P) perspective in a company which has a reputable brand at an international level. The research also tries to discover the missing link between Strategy-as-Practice and HRM. In addition, the study tries to explain how S-as-P and HR interact and work together. This study was performed as a case study through using qualitative research methods. In the research, interview techniques which are semi-structured and open-ended questioning was used. The sample of the study is composed of HR directors, Strategic Planning directors and employees. This study is original in the nature as it tries to discuss Strategic HR from strategy as practice perspective. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Human Resource Management; Strategic HR; Strategy-as-practice; Reflexivity; Reputation Management; HUMAN-RESOURCE MANAGEMENT; DESIGN; FIRM